DIDACTIC GAMES AS A TOOL FOR DEVELOPING LOGICAL OPERATIONS IN CHILDREN AGED 5–7: THEORETICAL ASPECTS (British Journal of Global Ecology and Sustainable Development, 2026)
This article examines the role of didactic games in the formation of fundamental logical operations—such as analysis, synthesis, comparison, and classification—in senior preschool-aged children. Particular attention is given to the analysis of the regulatory and legal framework of the Republic of Uzbekistan within the preschool education sector, as well as the theoretical substantiation of the effectiveness of game-based methods. The authors emphasize the significance of continuity between preschool and primary general education through the advancement of cognitive abilities.